Encourage Research Thinking in Network Domain Using Traffic Analysis Tool - Desai, Padmashree; Vijayalakshmi, M.; Raikar, Meenaxi M. (Journal of Engineering Education Transformations, 2017)
Explosive growth of Computer network technologies and use of these technologies have led a new thinking for researcher. In recent days the research focus in network domain is on areas like, Performance measurement of broadband and mobile access networks, Censorship measurement and circumvention, Software-defined networking (SDN), Internet of Things (IoT) security. This has created a challenge to the academicians to make students think towards these research fields and to adopt activity based teaching learning techniques to deliver the basics as well as the advanced concepts of computer network. As most of the students are visual learner teaching computer networking principles can be enhanced using simulation through the use of interactive simulation. With networking simulation tools, students can construct, tune, and analyze network performance while reinforcing their understanding of networking theory. The course expects the students should have an ability to understand the concepts, design and analyze the performance of the network. Experience of authors says that have an ability to understand the network concepts but they lack in analysis. So authors have put effort to address the lacunae. The activity has been designed by integrating theory and laboratory course on computer network which focuses on network traffic analysis by applying the concepts learnt. Wire Shark traffic analysis tool is used by students to capture the real time data and analyze the data for the selected network protocol. The paper discusses the design, conduction of activity, in computer network course focusing on analysis on network traffic which in turn created a space to think on research related to the network domain. Through this activity we could attain course outcome 3 and Program outcome (PO) 4 and 5 which is more than 80%.